1992
DOI: 10.1111/j.1471-4159.1992.tb11383.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Elements of the Rat Choline Acetyltransferase Gene Allowing Nerve Growth Factor Inducibility in Transfected Primary Cultured Cells

Abstract: Choline acetyltransferase, the enzyme responsible for the synthesis of acetylcholine, provides a convenient index for cholinergic neurons. Using a previously identified rat cDNA clone, we have isolated several corresponding genomic clones and have characterized a 1,902-bp fragment that contains part of the first noncoding exon as well as promoter sequences. The promoter activity of this fragment was tested, taking advantage of the recently developed lipopolyamine-mediated DNA transfer method, which allows tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…The sequences of the corresponding exons, numbered 1 and 2, were identical with those previously reported (Hersh et al, 1989;Toussaint et al, 1992). A 1.9-kb Hind111 rat genomic fragment (Bejanin et al, 1992) ern blots of human cosmid DNA at moderate stringency. The probe labeled a 1.7-kbp ApaI-XhoI fragment, which was located from 8.1 to 6.4 kbp upstream of exon 1, and included the human homolog of rodent exon R. A dotplot comparison of the sequence of the ApaI-XhoI fragment with the published rat genomic sequence (Ibaiiez et al, 1991;Bejanin et al, 1992) is presented on Figure 2B.…”
Section: Localization Of 5' Exonsmentioning
confidence: 90%
“…The sequences of the corresponding exons, numbered 1 and 2, were identical with those previously reported (Hersh et al, 1989;Toussaint et al, 1992). A 1.9-kb Hind111 rat genomic fragment (Bejanin et al, 1992) ern blots of human cosmid DNA at moderate stringency. The probe labeled a 1.7-kbp ApaI-XhoI fragment, which was located from 8.1 to 6.4 kbp upstream of exon 1, and included the human homolog of rodent exon R. A dotplot comparison of the sequence of the ApaI-XhoI fragment with the published rat genomic sequence (Ibaiiez et al, 1991;Bejanin et al, 1992) is presented on Figure 2B.…”
Section: Localization Of 5' Exonsmentioning
confidence: 90%
“…These mRNA isoforms appear to be generated from either a transcriptional start site upstream of the R exon, which may also be used for ChAT, or from sites within the VAChT exon (Bejanin et al, 1992;Misawa et al, 1992;Kengaku et al, 1993;Alfonso et al, 1994;Cervini et al, 1995), Fig. 1.…”
Section: Genomic Structure and Transcription Of The Cholinergic Gene mentioning
confidence: 98%
“…A variety of neurotrophic factors, including nerve growth factors (NGF), are known to participate in the regulation of ChAT mRNA expression (Bejanin et al, 1992;Cavicchioli et al, 1991;Cervini et al, 1994;Misawa et al, 1993;Nawa et al, 1991;Pedersen et al, 1995). By using an antiserum against VAChT, Takei et al (1997a) reported that NGF and brain-derived neurotrophic factor (BDNF) increased the number of immunoreactive neurons and enhanced immunoreactivity in cultured rat embryonic septal cells.…”
Section: Introductionmentioning
confidence: 98%